Appropriate extent of surgery for aspirin‐exacerbated respiratory disease. Issue 4 (1st December 2020) - Muhonen, Ethan G.; Goshtasbi, Khodayar; Papagiannopoulos, Peter; Kuan, Edward C.
Abstract : The current literature lacks strong guidelines regarding surgical management of patients with aspirin‐exacerbated respiratory disease (AERD), who present with the clinical triad of chronic rhinosinusitis with nasal polyposis (CRSwNP), bronchial asthma, and aspirin/nonsteroidal anti‐inflammatory drug intolerance. To further define the effectiveness of sinus surgery in treating AERD patients, this review article discusses current evidence regarding outcomes associated with more extensive surgery, the benefits of frontal sinus surgery on polyposis, and the role of Draf III intervention. Numerous studies suggest that Draf III frontal sinusotomy may be an efficacious early intervention due to increased neo‐ostial patency and subsequent distribution of topical therapies. Future studies that further investigate the efficacy and safety of extensive surgery in AERD patients are warranted.